Osteoid Osteoma of Distal Phalanx of Toe: A Rare Cause of Foot Pain - EROL, BÜLENT; TOPKAR, OSMAN MERT (My University, 2014)
Osteoid osteoma is an uncommon benign tumor and causes severe pain, being worse at night, that responds dramatically to nonsteroidal anti-inflammatory medications. An osteoid osteoma of the toe is very rare and arising in a pedal phalanx may be difficult to diagnose. A 34-year-old male has local swelling and tenderness but there were no hyperemia, temperature increase, or clubbing. There was a 2-month history of antibiotic treatment with suspicion of soft tissue infection in another clinic. The osteoid osteoma was completely excised by curettage and nidus removal with open surgical technique. The patient was followed up for 63 months with annual clinical and radiographic evaluations. There was no relapse of the pain and no residual recurrent tumour. Osteoid osteoma may be difficult to distinguish from chronic infection or myxedema. The patients may be taken for unnecessary treatment. The aim of the treatment for osteoid osteoma is to remove entire nidus by open surgical excision or by percutaneous procedures such as percutaneous radiofrequency and laser ablation. Osteoid osteomas having radiologic and clinical features other than classical presentation of osteoid osteoma are called atypical osteoid osteomas. Atypical localized osteoid osteomas can be easily misdiagnosed and treatment is often complicated.